Analisis Knowledge Management dan Budaya Kerja terhadap Kinerja Karyawan pada PT. Bank BCA KCU Darmo Surabaya - Sisillia Evelyn Tjusanto; Gendut Sukarno (UNHI Press, 2021)
This research was carried out at PT. Bank BCA KCU Darmo, Surabaya City, East Java province. Based on research results of BCA Policy data related to HR development and employee protection, it can be seen that BCA guarantees HR development and implements policies to protect its employees within the organization. The intention was to determine whether knowledge management and work culture influence employee performance at PT. Bank BCA KCU Darmo Surabaya City. The population used in this study were all workers of PT. Bank BCA KCU Darmo Surabaya City amounted to 30 respondents as a sample. The analytical technique used in this research is smart partial least square (PLS). The analysis results show that knowledge management and work culture can make a significant role in the performance of employees of PT. Bank BCA KCU Darmo Surabaya City.